Large-area coated lithium manganate positive electrode material and preparation method thereof

By performing grain boundary pretreatment and large-area coating on lithium manganate positive electrode material, the problems of unstable structural structure and uneven surface coating at high temperatures are solved, and its high-temperature circulation and storage performance are significantly improved.

CN119833624APending Publication Date: 2025-04-15XIANGTAN ELECTROCHEMICAL SCI CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510042658.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The spinel structure of lithium manganate positive electrode material is prone to expose the (111) crystal surface dissolved by Mn, resulting in a degradation of high-temperature circulation and storage performance, and the surface cladding layer is prone to breaking and falling off, making it difficult to achieve large-area uniform cladding.

Method used

Through grain boundary pretreatment, doped elements such as La, W, Mo, etc. are used to modify the lithium manganate structure to induce the growth of the dominant crystal surface and reduce the surface energy. Combined with the construction of the surface cladding layer, large-area cladding is achieved.

Benefits of technology

It significantly improves the high-temperature circulation and storage performance of lithium manganate positive electrode material, enhances structural stability, alleviates electrolyte corrosion, inhibits Mn dissolution, and has a simple process and can be produced on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833624A_ABST
    Figure CN119833624A_ABST
Patent Text Reader

Abstract

The invention provides a large-area coated lithium manganate positive electrode material and a preparation method thereof, and belongs to the technical field of energy materials, and the large-area coated lithium manganate positive electrode material comprises a lithium manganate positive electrode material body subjected to grain boundary pretreatment and a coating layer coating the surface of the lithium manganate positive electrode material body. The general molecular formula of the lithium manganate positive electrode material body subjected to grain boundary pretreatment is Li < 1 + a > Mn < 2-b > MbO4, M is a doping element, a is more than or equal to-0.1 and less than or equal to 0.3, and b is more than or equal to 0 and less than or equal to 0.3; the surface coating layer comprises an M'coating element. The lithium manganate positive electrode material body subjected to grain boundary pretreatment can realize large-area coating, and the lithium manganate positive electrode material subjected to special grain boundary pretreatment and large-area coating has excellent structural stability, so that corrosion of an electrolyte to lithium manganate is relieved, Mn dissolution at a high temperature is inhibited, and the lithium manganate positive electrode material has good electrochemical performance. Therefore, the lithium manganate positive electrode material has excellent high-temperature circulation and high-temperature storage performance, and the method is simple in process and can be implemented and popularized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of energy materials, and in particular relates to a large-area coated lithium manganese oxide positive electrode material and a preparation method thereof. Background Art

[0002] Lithium manganate cathode material (LiMn 2 O 4 ) There is Mn 3+ The Jahn-Teller effect caused by Mn leads to the structural stability of lithium manganese oxide and the deterioration of cycle performance; 3+ To Mn 2+ The disproportionation reaction of lithium manganate leads to the destruction of the spinel structure of lithium manganate. 2+ Deposition on the negative electrode surface destroys the interface structure of the negative electrode material such as SEI, which will lead to a significant decrease in the capacity and cycle life of lithium manganese oxide; in addition, due to the trace water in the electrolyte, the electrolyte decomposes into HF, which further triggers Mn dissolution. These side reactions are more obvious at high temperatures, thereby deteriorating the high-temperature cycle and storage performance of lithium manganese oxide positive electrode materials. In order to solve these problems of lithium manganese oxide, the main research directions are doping modification and surface coating to improve the cycle performance of lithium manganese oxide. Doping is mainly to improve the stability of the Mn-O octahedral structure by doping other metals or non-metallic elements in the lithium manganese oxide structure, and to inhibit the structural changes caused by the Jahn-Teller effect; surface coating modification is mainly to alleviate HF corrosion and Mn dissolution, and promote the formation of a uniform SEI film. However, simple doping modification can effectively improve the structural stability of lithium manganese oxide, but the spinel structure of lithium manganese oxide is prone to expose a large number of (111) crystal planes that are prone to Mn dissolution, which is not conducive to the high-temperature cycle of lithium manganese oxide. In addition, the spinel structure of lithium manganese oxide has a high surface energy, which easily causes the surface coating layer to break and fall off, which is not conducive to achieving large-area and uniform surface coating modification. Summary of the invention

[0003] The embodiments of the present application provide a large-area coated lithium manganese oxide positive electrode material and a preparation method thereof, which aims to solve to a certain extent the problem that the spinel structure of lithium manganese oxide is prone to expose a large number of (111) crystal planes from which Mn has been dissolved, which is not conducive to the high-temperature cycle and storage of lithium manganese oxide.

[0004] In the first aspect, the present invention provides a large-area coated lithium manganese oxide positive electrode material, including a lithium manganese oxide body pretreated by grain boundaries and a surface coating layer, wherein the molecular formula of the lithium manganese oxide body pretreated by grain boundaries is Li 1+a Mn 2- b M b O 4, wherein M is a doping element, wherein -0.1≤a≤0.3, 0≤b≤0.3, and the surface coating layer contains M' element.

[0005] In some embodiments, the doping element M for grain boundary pretreatment is a combination of one or more of La, W, Mo, Ce, Eu, Ge, In, Sm, Zr, Ti, Gd, Ga, Nd, Ta, Ba, Sb, Nb, V, Y, Sr or Yb.

[0006] In some embodiments, the surface coating layer is a combination of one or more of an oxide, fluoride, hydroxide, phosphate, carbonate, sulfate, nitrate, chloride, acetate, conductive polymer and a positive electrode material of a lithium ion battery containing an M' element, wherein M' is a combination of one or more of C, H, O, N, P, S, B, F, Mg, La, Si, Nb, Co, Eu, Ta, Al, Yb, Zr, Li, Sr, Ge, Ti, Ce, Sb, Ni, Y, Sn, Ru, V, In, Cu, Mn, Mo or W. The molecular formula of the positive electrode material of the lithium ion battery is Li 1+i (TM) x PO 4 and / or Li 1+i (TM) x O 2 , wherein TM is one or more transition metal elements, and 0≤i≤0.3, 0≤x≤1.

[0007] Through the M element La, W, Mo, Ce, Eu, Ge, In, Sm, Zr, Ti, Gd, Ga, Nd, Ta, Ba, Sb, Nb, V, Y, Sr or Yb, one or more of them are doped and modified to pre-treat the grain boundaries, effectively improving the stability of the lithium manganate structure, inducing the growth of the dominant crystal plane of the lithium manganate spinel and increasing the dominant grain boundary ratio, while the doping elements react with different lithium salts to form molten salts, thereby regulating the size and morphology of the primary particles of lithium manganate; reducing the activation energy and surface energy of the grain boundaries of the primary particles of the lithium manganate positive electrode material, further reducing the specific surface area and reducing the interface side reactions, and improving the electron and ion transport kinetics of the grain boundaries. On this basis, the surface coating layer of the lithium manganate positive electrode material is constructed, and the controllable large-area coating of the lithium manganate surface can be achieved. The lithium manganate after grain boundary pretreatment is conducive to large-area and uniform surface coating, and the coating material can be selected independently. The coating material selected in this application includes common oxides and other coating materials, as well as conductive polymers and lithium ion battery positive electrode materials.

[0008] Surface coating based on the above modified layer is helpful to improve high temperature performance. The high temperature cycle and storage performance of lithium manganese oxide positive electrode materials will be significantly improved, and the cycle stability and high temperature cycle and storage performance of lithium manganese oxide positive electrode materials are effectively improved. The preparation process of the lithium manganese oxide positive electrode material is simple, the manufacturing cost is low, and it can be mass-produced.

[0009] Only after pretreatment of the grain boundaries with various doping elements can large-area coating be achieved, and the performance will be better. Large-area and uniform coating cannot be achieved without crystal surface induction, and only grain boundary pretreatment cannot guarantee the high-temperature cycle and storage of lithium manganese oxide. Lithium manganese oxide positive electrode materials with special grain boundary pretreatment and large-area coating have excellent structural stability, alleviate electrolyte corrosion to lithium manganese oxide, and inhibit Mn dissolution at high temperatures. Therefore, lithium manganese oxide positive electrode materials have excellent high-temperature cycle and high-temperature storage performance, and this method is simple in process and can be implemented and promoted.

[0010] In a second aspect, an embodiment of the present application provides a method for preparing the large-area coated lithium manganese oxide positive electrode material according to the first aspect, comprising the following steps:

[0011] S1. Doping a doping substance containing the M element in a manganese-containing compound through a doping process to obtain a precursor containing the M element;

[0012] S2, mixing the precursor containing the M element with a lithium salt, and performing a first sintering to prepare grain boundary pretreated lithium manganese oxide;

[0013] S3, coating the surface coating layer onto the surface of the grain boundary pretreated lithium manganese oxide through a coating process, and performing a second sintering to obtain a large-area coated lithium manganese oxide positive electrode material.

[0014] It can be understood that the beneficial effects of the second aspect mentioned above can be found in the relevant description of the first aspect mentioned above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0016] Figure 1 This is a SEM image of a large-area coated lithium manganese oxide positive electrode material in Example 1;

[0017] Figure 2 This is the XRD diagram of the grain boundary pretreatment and large-area coating of lithium manganate positive electrode material in Example 1;

[0018] Figure 3 TEM image of grain boundary pretreatment and large-area coating of lithium manganate positive electrode material in the embodiment;

[0019] Figure 4 This is the SEM image of the lithium manganese oxide positive electrode material of Comparative Example 1;

[0020] Figure 5 This is the TEM image of the lithium manganese oxide positive electrode material of comparative example 1. DETAILED DESCRIPTION

[0021] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0022] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0023] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.

[0024] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0026] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.

[0027] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0028] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0030] In a first aspect, the present invention provides a large-area coated lithium manganate positive electrode material, the structure of the lithium manganate positive electrode material comprises a lithium manganate body after grain boundary pretreatment and a large-area surface coating layer, the molecular formula of the lithium manganate body after grain boundary pretreatment is Li 1+a Mn 2-b M b O 4 , the M is a doping element for grain boundary pretreatment, wherein -0.1≤a≤0.3, 0≤b≤0.3; the surface coating layer contains M' element.

[0031] Only after grain boundary pretreatment can the lithium manganese oxide body be coated over a large area. The lithium manganese oxide body without grain boundary pretreatment cannot be coated over a large area with controllable coating thickness. Only grain boundary pretreatment cannot guarantee the high-temperature cycle and storage of lithium manganese oxide. The lithium manganese oxide positive electrode material with special grain boundary pretreatment and large-area coating has excellent structural stability, alleviates the corrosion of the electrolyte to lithium manganese oxide, and inhibits the dissolution of Mn at high temperature. Therefore, the lithium manganese oxide positive electrode material has excellent high-temperature cycle and high-temperature storage performance, and the method is simple in process and can be implemented and promoted.

[0032] In some embodiments, the doping element M for grain boundary pretreatment is a combination of one or more of La, W, Mo, Ce, Eu, Ge, In, Sm, Zr, Ti, Gd, Ga, Nd, Ta, Ba, Sb, Nb, V, Y, Sr or Yb.

[0033] In some embodiments, the surface coating layer is a combination of one or more of an oxide, fluoride, hydroxide, phosphate, carbonate, sulfate, nitrate, chloride, acetate, a conductive polymer and a lithium-ion battery positive electrode material containing an M' element, and the M' is a combination of one or more of C, H, O, N, P, S, B, F, Mg, La, Si, Nb, Co, Eu, Ta, Al, Yb, Zr, Li, Sr, Ge, Ti, Ce, Sb, Ni, Y, Sn, Ru, V, In, Cu, Mn, Mo or W.

[0034] In some embodiments, the molecular formula of the lithium-ion battery positive electrode material is Li 1+i (TM) x PO 4 and / or Li 1+i (TM) x O 2 , wherein TM is one or more transition metal elements, and 0≤i≤0.3, 0≤x≤1.

[0035] In a second aspect, the present invention further provides a method for preparing a large-area coated lithium manganese oxide positive electrode material as described in the first aspect, comprising the following steps:

[0036] S1. Doping a doping substance containing the M element in a manganese-containing compound through a doping process to obtain a precursor containing the M element;

[0037] S2, mixing the precursor containing the M element with a lithium salt, and performing a first sintering to prepare a lithium manganate body with grain boundary pretreatment;

[0038] S3, coating the surface coating layer onto the surface of the lithium manganese oxide body with pre-treated grain boundaries through a coating process, and performing a second sintering to obtain a large-area coated lithium manganese oxide positive electrode material.

[0039] In some embodiments, the manganese-containing compound in step S1 is Mn 3 O 4 、MnO 2 , Mn 2 O 3 、MnOOH、MnCO 3 、MnSO 4 , (CH 3 COO 2 Mn、Mn(NO 3 ) 2 and MnC 2 O 4 A combination of one or more of .

[0040] In some embodiments, the doping material containing element M in step S1 is one or more of oxides, fluorides, hydroxides, carbonates, sulfates, nitrates, chlorides, acetates or phosphates containing element M; the doping process in step S1 includes a solid phase method or a liquid phase method, and the solid phase method includes a combination of one or more of ball milling, high mixing or oblique mixing; the liquid phase method includes a combination of one or more of sol-gel method, hydrothermal method, co-precipitation method or spray drying method.

[0041] In some embodiments, the lithium salt in step S2 includes a combination of one or more of lithium hydroxide, lithium carbonate, lithium fluoride, lithium sulfate, lithium phosphate and lithium nitrate; the first sintering process parameters are: one-step sintering or multi-step sintering, a heating rate of 1 to 5°C / min, a sintering temperature of 300 to 900°C, and a sintering time of 1 to 30h.

[0042] In some embodiments, the coating process in step S3 includes a solid phase method or a liquid phase method, and the solid phase method includes a combination of one or more of ball milling, high mixing or oblique mixing; the liquid phase method is a combination of one or more of sol-gel method, hydrothermal method, co-precipitation method or spray drying method.

[0043] In some embodiments, the process parameters of the second sintering include one-step sintering or multi-step sintering, in an atmosphere of air, oxygen or nitrogen, a heating rate of 1 to 10°C / min, a sintering temperature of 300 to 1000°C, and a sintering time of 1 to 24h.

[0044] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.

[0045] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.

[0046] Example 1

[0047] A method for preparing a large-area coated lithium manganese oxide positive electrode material comprises the following steps:

[0048] S1: Add 10L pure water as the base liquid to a 50L reactor, control the stirring speed to 500rpm, and maintain a constant temperature of 60°C. Then, add manganese sulfate solution, zirconium sulfate solution, and ammonia solution to the reactor, control the molar ratio of manganese sulfate to zirconium sulfate to 200:1, and then slowly introduce 9mol / L ammonia solution into the reactor to keep the ammonia concentration and pH in the reactor at 11, and continuously react to synthesize the slurry-doped Zr-manganese tetraoxide precursor. Then, after washing and filtering the slurry with deionized water, dry it at 120°C in a blast drying oven for 12h to obtain a Zr-doped spherical manganese tetraoxide precursor with a particle size D50 of 8μm.

[0049] S2. The obtained Zr-doped spherical manganese tetraoxide precursor is placed in a high-speed mixer and mixed with lithium hydroxide, wherein the molar ratio of lithium to manganese is maintained at 0.53, the mixed material is placed in a bowl in an orbital kiln for sintering, and calcined at 800° C. for 18 hours in a compressed air atmosphere to obtain a Zr-doped grain boundary pretreated lithium manganate positive electrode material.

[0050] S3, dissolving aluminum nitrate in deionized water, and adjusting the solution pH to 2.5 with nitric acid to obtain a first solution; dissolving ammonium dihydrogen phosphate in deionized water to obtain a second solution; adding the Zr-doped grain boundary pretreated lithium manganese oxide positive electrode material obtained above to the first solution, stirring for 3 hours, and obtaining a third slurry; slowly passing the second solution into the third slurry at a flow rate of 1L / h, stirring at a speed of 500r, maintaining a constant temperature of 80°C, and reacting continuously for 2 hours, filtering, washing, and drying the slurry, and annealing the obtained material at 600°C for 4 hours, and the calcination atmosphere is compressed air, so as to obtain Zr-doped grain boundary pretreated and AlPO 4 Large-area coated lithium manganese oxide positive electrode material.

[0051] Figure 1 This is a SEM image of a large-area coated lithium manganese oxide positive electrode material in Example 1. It can be seen that the surface particles of the lithium manganese oxide positive electrode material are smooth after crystal surface pretreatment and surface coating;

[0052] Figure 2 This is the XRD diagram of the lithium manganese oxide positive electrode material with grain boundary pretreatment and large-area coating in Example 1. It can be seen that the XRD diffraction signal of the lithium manganese oxide positive electrode material after crystal surface pretreatment and surface coating corresponds to the standard card PDF#70-3120 of lithium manganese oxide;

[0053] Figure 3 This is the TEM image of the lithium manganese oxide positive electrode material with grain boundary pretreatment and large-area coating in the embodiment. It can be seen that a large-area and uniform coating layer is attached to the surface of the lithium manganese oxide positive electrode material after crystal surface pretreatment and surface coating, which will be beneficial to inhibit Mn dissolution and greatly improve the high-temperature performance of the lithium manganese oxide positive electrode material.

[0054] Example 2

[0055] A method for preparing a large-area coated lithium manganese oxide positive electrode material comprises the following steps:

[0056] S1: First, add 10L pure water as the base liquid to a 50L reactor, control the stirring speed to 500rpm, and maintain a constant temperature of 60°C. Then, add manganese sulfate solution and ammonia solution to the reactor, and then slowly introduce 9mol / L ammonia solution into the reactor to keep the ammonia concentration and pH in the reactor at 11, and continuously react to synthesize the precursor slurry of manganese tetraoxide. Then, after washing and filtering the slurry with deionized water, dry it at 120°C in a blast drying oven for 12h to obtain a spherical manganese tetraoxide precursor with a particle size D50 of 8μm; place the spherical manganese tetraoxide precursor with a particle size D50 of 8μm and lithium hydroxide in a ball mill at a Li / Mn ratio of 0.53, and then add MoO with a Mo element doping amount of 3000ppm. 3 , obtaining a mixture of a precursor, a doping material containing the Mo element and a lithium salt;

[0057] S2. The precursor, the doping material containing the Mo element and the mixture of the lithium salt are mixed at a high speed of 300 r / min for 6 hours, and the mixed powder is calcined at 800° C. for 18 hours to obtain a Mo-doped grain boundary pretreated lithium manganese oxide positive electrode material.

[0058] S3: Dissolve aluminum nitrate in deionized water, and adjust the solution pH to 2.5 with nitric acid to obtain the first solution; dissolve ammonium dihydrogen phosphate in deionized water to obtain the second solution; add the Mo-doped grain boundary pretreated lithium manganese oxide positive electrode material obtained above to the first solution, stir for 3 hours, and obtain the third slurry; slowly pass the second solution into the third slurry at a flow rate of 1L / h, stir at a speed of 500r, maintain a constant temperature of 80°C, react continuously for 2 hours, filter, wash, and dry the slurry, anneal the obtained material at 600°C for 4 hours, and use compressed air as the calcination atmosphere to obtain Mo-doped grain boundary pretreated and AlPO 4 Large-area coated lithium manganese oxide positive electrode material.

[0059] Example 3

[0060] A method for preparing a large-area coated lithium manganese oxide positive electrode material comprises the following steps:

[0061] S1: First, add 10L pure water as the base liquid to a 50L reactor, control the stirring speed to 500rpm, and maintain a constant temperature of 60°C. Then, add manganese sulfate solution and ammonia solution to the reactor, and then slowly introduce 9mol / L ammonia solution into the reactor to keep the ammonia concentration and pH in the reactor at 11, and continuously react to synthesize the precursor slurry of manganese tetraoxide. Then, after washing and filtering the slurry with deionized water, dry it at 120°C in a blast drying oven for 12h to obtain a spherical manganese tetraoxide precursor with a particle size D50 of 8μm; place the spherical manganese tetraoxide precursor with a particle size D50 of 8μm and lithium hydroxide in a ball mill at a Li / Mn ratio of 0.53, and then add MoO with a Mo element doping amount of 3000ppm. 3 , obtaining a mixture of a precursor, a doping material containing the Mo element and a lithium salt;

[0062] S2. The precursor, the doping material containing the Mo element and the mixture of the lithium salt are mixed at a high speed of 300 r / min for 6 hours, and the mixed powder is calcined at 800° C. for 18 hours to obtain a Mo-doped grain boundary pretreated lithium manganese oxide positive electrode material.

[0063] S3: The Mo-doped grain boundary-regulated lithium manganese oxide positive electrode material obtained above is mixed with Al 2 O 3 The materials were mixed in a high-speed mixer at 300 r / min for 5 min, and then the speed was increased to 800 r / min for 20 min to obtain a mixed powder. The powder was then put into a bowl and annealed at 600 °C in an air atmosphere for 6 h to obtain Mo-doped grain boundary pretreatment and Al-doped grain boundary pretreatment. 2 O 3 Large-area coated lithium manganese oxide positive electrode material.

[0064] Example 4

[0065] A method for preparing a large-area coated lithium manganese oxide positive electrode material comprises the following steps:

[0066] S1, which is different from Example 1, is that in this step, electrolytic manganese dioxide is used as a precursor, the precursor is uniformly mixed with lithium hydroxide in a high-speed mixer at a Li / Mn ratio of 0.53, and then WO with a W doping amount of 3000 ppm is added thereto. 3 After the powder is formed, a mixture of the precursor, the doping material containing the W element and the lithium salt is obtained;

[0067] S2. Mix the above-mentioned precursor, the doping material containing the W element and the lithium salt at a stirring rate of 500 r / min for 10 minutes, then increase the speed to 800 r / min and mix for 30 minutes to obtain a mixed powder, and then calcine the mixed powder at 800° C. for 18 hours to obtain a W-doped grain boundary pretreated lithium manganese oxide positive electrode material.

[0068] S3: The W-doped grain boundary-regulated lithium manganese oxide positive electrode material obtained above is combined with Al 2 O 3 The material was mixed in a ball mill at 400 r / min for 6 h, and then the powder was put into a bowl and annealed at 600 °C in air for 4 h to obtain the W-doped grain boundary pretreatment and Al 2 O 3 Large-area coated lithium manganese oxide positive electrode material.

[0069] Embodiment 5~7:

[0070] Different from Example 1, the relevant parameters and substances in the preparation steps of the positive electrode active material are changed to obtain a positive electrode active material with predetermined parameter characteristics.

[0071] In step S2 of embodiments 5 to 7, the lithium source and the coating material are respectively lithium carbonate and MgO;

[0072] The coating process of step S3 of embodiments 5 to 7 adopts solid phase coating;

[0073] The sintering schedule of step S3 of Examples 5 to 7 is sintering at 500° C. for 6 hours.

[0074] Wherein Examples 1-3, 5-6 are Mn 3 O 4 Precursor, Examples 4 and 7 are undoped MnO 2 Precursor, wherein Examples 1 and 5 are liquid phase doped Mn 3 O 4 .

[0075] The types and contents of the doping elements and coating materials of the examples are shown in Table 1.

[0076] Table 1: Sample information of the examples

[0077]

[0078]

[0079] Comparative Examples 1 to 10:

[0080] The difference from Example 1 is that the relevant parameters and substances in the preparation steps of the positive electrode active material are changed to obtain a positive electrode active material with predetermined parameter characteristics, and the other operations are the same.

[0081] Among them, comparative examples 1 to 4, 7 and 9 are Mn 3 O 4 Precursor, comparative examples 5 to 6, 8 and 10 are MnO 2 Precursor;

[0082] Among them, comparative example 2 is a liquid phase method to dope Mn 3 O 4 Precursor.

[0083] The types and contents of the doping elements and coating materials of the comparative example are shown in Table 2.

[0084] Table 2: Sample information of comparative example

[0085]

[0086] Figure 4 This is a SEM image of the lithium manganese oxide positive electrode material of Comparative Example 1, without crystal surface pretreatment. It can be seen from the image that the primary particles of the lithium manganese oxide positive electrode material without surface pretreatment are spinel morphology;

[0087] Figure 5 This is the TEM image of the lithium manganese oxide positive electrode material of comparative example 1, without crystal surface pretreatment. It can be seen from the figure that the primary particles of the lithium manganese oxide positive electrode material without surface pretreatment are spinel morphology. Due to the strong interface energy, an uneven surface coating layer is formed, which is not conducive to the high-temperature cycle and storage of the lithium manganese oxide positive electrode material.

[0088] Test example:

[0089] 1. Preparation of button cell

[0090] The multifunctional layer lithium manganese oxide positive electrode material, conductive carbon black and binder PVDF prepared above are dispersed in solvent N-methylpyrrolidone (NMP) in a weight percentage of 95:3:2 and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.

[0091] In a button battery box, the positive electrode sheet, the isolation membrane and the metal lithium sheet are stacked in sequence, and the above-mentioned electrolyte is injected to assemble a button battery.

[0092] 2. Preparation of full battery

[0093] The positive electrode active material, conductive agent acetylene black and binder PVDF prepared above were dispersed in solvent NMP at a weight percentage of 95:3:2 and mixed evenly to obtain positive electrode slurry; the positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.

[0094] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener carbon methyl cellulose sodium (CMC) are dispersed in deionized water in a weight percentage of 90:5:2:2:1 and mixed evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector aluminum foil, and after drying and cold pressing, a negative electrode sheet is obtained.

[0095] A polypropylene (PP) porous polymer film is used as a separator. The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order to obtain a bare cell, which is placed in an outer package, injected with the above electrolyte and packaged, and after a formation process, a full battery is obtained.

[0096] 3. Test part

[0097] (1) Initial gram capacity test of button cell

[0098] At 60°C, charge the battery at a constant current of 0.2C to a charge cut-off voltage of 4.3V, then charge at a constant voltage to a current less than or equal to 0.01C, then jump to the rest step, the battery is left for 2 minutes, and then discharged at a constant current of 0.2C to a discharge cut-off voltage of 3.0V. The discharge capacity at this time is the initial gram capacity of the button battery.

[0099] (2) Initial gram capacity test of full battery

[0100] At 25°C, charge the battery at a constant current of 0.2C to a charge cut-off voltage of 4.3V, then charge at a constant voltage to a current less than or equal to 0.01C, leave it for 5 minutes, and then discharge it at a constant current of 0.2C to a discharge cut-off voltage of 3.0V. The discharge capacity at this time is the initial gram capacity of the whole battery.

[0101] (3) High temperature cycle performance test of full battery

[0102] At 60°C, charge the battery at 1C constant current to a charge cut-off voltage of 4.3V, then charge at constant voltage to a current less than or equal to 0.01C, leave for 5 minutes, and then discharge at 1C constant current to a discharge cut-off voltage of 3.0V. This is a charge and discharge cycle, and the discharge capacity of this time is recorded as the discharge capacity D1 of the first cycle. Perform 100 cycle charge and discharge tests on the battery according to the above method, and record the discharge capacity D100 of the 100th cycle. Full battery at 60°C, 1C / 1C cycle 100 times capacity retention rate (%) = D100 / D1×100%

[0103] (4) High temperature storage performance test of full battery

[0104] At 60°C, a soft-pack battery with a designed capacity of 1Ah is charged at a constant current of 1C to 100% SOC state, with a cut-off voltage of 4.3V, and then charged at a constant voltage to a current less than or equal to 0.01C. The battery is then placed in a constant temperature box at 60°C and stored for 30 days. It is then discharged at a constant current of 1C to a discharge cut-off voltage of 3.0V, and the battery's discharge specific capacity D2 is recorded. The capacity retention rate of the full battery after 30 days of storage = D2 / 1Ah*100%.

[0105] In tests (1)-(4), in Examples 1-15 and Comparative Examples 1-14, the charge and discharge cut-off voltage of the button cell was 3.0V-4.3V, and the charge and discharge cut-off voltage of the full cell was 3.0V-4.3V;

[0106] The test data of button cells and full cells of Examples 1 to 7 and Comparative Examples 1 to 10 are shown in Table 3. The groups forming the performance comparison are: Example 1 and Comparative Examples 1 to 2, Example 2 and Comparative Examples 3 and 9, Example 3 and Comparative Examples 3 to 4, 6 and 9, Example 4 and Comparative Examples 5 to 6, 8 and 10, Example 5 and Comparative Examples 7 and 9, Example 6 and Comparative Examples 3, 7 and 9, and Example 7 and Comparative Examples 8 and 10.

[0107] The button cell and full cell test data of the embodiment and the comparative example are as follows:

[0108] Table 3: Test data of embodiments and comparative examples

[0109]

[0110] Through the comparison results of Examples 1 to 7 and Comparative Examples 1 to 10, it can be seen that the high-temperature capacity retention rate and storage performance of the whole battery of the lithium manganese oxide positive electrode material after crystal surface pretreatment combined with surface coating are significantly improved, indicating that the surface interface energy of the material is reduced after crystal surface pretreatment, which is conducive to large-area coating, thereby greatly improving the high-temperature performance of the lithium manganese oxide positive electrode material.

[0111] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0112] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A large-area coated lithium manganese oxide positive electrode material, characterized in that: The invention comprises a lithium manganate body after grain boundary pretreatment and a large-area surface coating layer, wherein the molecular formula of the lithium manganate body after grain boundary pretreatment is Li 1+a Mn 2-b M b O4, the M is a doping element for grain boundary pretreatment, wherein -0.1≤a≤0.3, 0≤b≤0.3; the surface coating layer contains M' element.

2. The large-area coated lithium manganate positive electrode material according to claim 1, characterized in that: The doping element M for the grain boundary pretreatment is a combination of one or more of La, W, Mo, Ce, Eu, Ge, In, Sm, Zr, Ti, Gd, Ga, Nd, Ta, Ba, Sb, Nb, V, Y, Sr or Yb.

3. The large-area coated lithium manganate positive electrode material according to claim 1, characterized in that: The surface coating layer is a combination of one or more of an oxide, fluoride, hydroxide, phosphate, carbonate, sulfate, nitrate, chloride, acetate, a conductive polymer and a positive electrode material of a lithium ion battery containing an M' element, and the M' is a combination of one or more of C, H, O, N, P, S, B, F, Mg, La, Si, Nb, Co, Eu, Ta, Al, Yb, Zr, Li, Sr, Ge, Ti, Ce, Sb, Ni, Y, Sn, Ru, V, In, Cu, Mn, Mo or W.

4. The large-area coated lithium manganate positive electrode material according to claim 3, characterized in that: The molecular formula of the positive electrode material of the lithium ion battery is Li 1+i (TM) x PO4 and / or Li 1+i (TM) x O2, wherein TM is one or more transition metal elements, wherein 0≤i≤0.3, 0≤x≤1.

5. A method for preparing a large-area coated lithium manganese oxide positive electrode material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Doping a doping substance containing the M element in a manganese-containing compound through a doping process to obtain a precursor containing the M element; S2, mixing the precursor containing the M element with a lithium salt, and performing a first sintering to prepare a lithium manganate body with grain boundary pretreatment; S3, coating the surface coating layer onto the surface of the lithium manganese oxide body after grain boundary pretreatment through a coating process, and performing a second sintering to obtain a large-area coated lithium manganese oxide positive electrode material.

6. The preparation method according to claim 5, characterized in that: The manganese-containing compound in step S1 is a combination of one or more of Mn3O4, MnO2, Mn2O3, MnOOH, MnCO3, MnSO4, (CH3COO)2Mn, Mn(NO3)2 and MnC2O4.

7. The preparation method according to claim 5, characterized in that: The doping material containing the M element in step S1 is one or more of an oxide, fluoride, hydroxide, carbonate, sulfate, nitrate, chloride, acetate or phosphate containing the M element; The doping process in step S1 includes a solid phase method or a liquid phase method, wherein the solid phase method includes a combination of one or more of a ball milling method, a high mixing method or an oblique mixing method; and the liquid phase method includes a combination of one or more of a sol-gel method, a hydrothermal method, a coprecipitation method or a spray drying method.

8. The preparation method according to claim 5, characterized in that: The lithium salt in step S2 includes one or more combinations of lithium hydroxide, lithium carbonate, lithium fluoride, lithium sulfate, lithium phosphate and lithium nitrate; The first sintering process parameters are: one-step sintering or multi-step sintering, a heating rate of 1 to 5°C / min, a sintering temperature of 300 to 900°C, and a sintering time of 1 to 30h.

9. The preparation method according to claim 5, characterized in that: The coating process in step S3 includes a solid phase method or a liquid phase method, wherein the solid phase method includes a combination of one or more of ball milling, high mixing or oblique mixing; and the liquid phase method is a combination of one or more of sol-gel method, hydrothermal method, coprecipitation method or spray drying method.

10. The preparation method according to claim 5, characterized in that: The process parameters of the second sintering include one-step sintering or multi-step sintering, in an atmosphere of air, oxygen or nitrogen, a heating rate of 1 to 10°C / min, a sintering temperature of 300 to 1000°C, and a sintering time of 1 to 24h.

Citation Information

Cited By

  • Manganese-based battery positive electrode material precursor and preparation method and application thereof

    CN120398122A

  • A manganese-based battery positive electrode material precursor and its preparation method and application

    CN120398122B

  • Manufacturing process of lithium iron phosphate energy storage battery

    CN121123420A

  • Quick-charging type spinel lithium manganate positive electrode material as well as preparation method and application thereof

    CN122051200A